Breast milk jaundice affects breastfeeding: From the perspective of intestinal flora and SCFAs-GPR41/43 - Huang, Huan; Huang, Juan; Huang, Wendi; Huang, Nanqu; Duan, Miao (Frontiers in Nutrition, 2023)
Breast milk jaundice (BMJ) is one of the main factors leading to interruption or early termination of breastfeeding. Interrupting breastfeeding to treat BMJ may increase the adverse consequences for infant growth and disease prevention. The Intestinal flora and metabolites are increasingly recognized as a potential therapeutic target in BMJ. First, dysbacteriosis can lead to a decrease in the metabolite short-chain fatty acids. At the same time, SCFA can act on specific G protein-coupled receptors 41 and 43 (GPR41/43), and a decrease in SCFA downregulates the GPR41/43 pathway, leading to a diminished inhibition of intestinal inflammation. In addition, intestinal inflammation leads to a decrease in intestinal motility and a large amount of bilirubin enters the enterohepatic circulation. Ultimately, these changes will result in the development of BMJ. In this review, we will describe the underlying pathogenetic mechanism of the Intestinal flora effects on BMJ.